Act of Incorporation and By-Laws of the Village of Northfield Page 20, Image 20 (1894) [Ordinances of the Village of Northfield,] By-Laws, Article XVII, Shooting with Firearms, § 1. - (:unkn) unknown (My University, 1894)
No person shall be allowed to shoot with fire-arms at a mark or otherwise, unless upon his own premises, and then in such a manner that the range of his shot shall be confined to his own grounds, under a penalty of five dollars for each offence. Provided that any person may shoot blank charges upon days of public celebration.
Keywords: DISCHARGE